THIRST TWEETS: WOMEN’S LANGUAGE USED TO SEXUALLY OBJECTIFY MEN - Sukma, Danti Permata; Anugerahwati, Mirjam; Yannuar, Nurenzia (J-ELLiT (Journal of English Language, Literature, and Teaching), 2022)
This study explores thirst tweets as sexual objectification with women as the writers and men as the targets, and the reason this phenomenon is allowed by society. As a new trend by BuzzFeed, thirst tweets are a set of tweets where mostly women compliment celebrities’ bodies. The data were gathered from a playlist video under the account BuzzFeed Celeb on YouTube. Firstly, Fairclough’s (2013) CDA and Langton’s (2009) Sexual Objectification theories were used to analyze the social relations of thirst tweets with sexual objectification. Secondly, watching the celebs’ reactions and comparing it to Berdahl et al. (1996) answered public’s tolerance in objectifying men. The results show that the construction of thirst tweets is in the form of reducing to the body and appearance, using violent language, and calling the celebs ‘daddy’. Also, the celebrities’ reactions and power play an important part in that the objectification is justifiable. While few felt uncomfortable, the male celebs still act polite by thanking the writers. Writers, as the consumers in a fandom, felt they are entitled to objectify these celebrities.